ANALISIS KUALITAS REPAIR WELDING METODE MIG DENGAN PELAKUAN PREHEATING DAN VARIASI ARUS PENGELASAN PADA CAST WHEEL ALUMINIUM - Eko Budi Susilo; Budi Harjanto; Suharno Suharno (Nozel : Jurnal Pendididikan Teknik Mesin, 2021)
The aim of this study are: (1) to identify the chemical composition of the aluminum cast wheel; (2) to identify the shape of the microstructure in the MIG welding method with preheating treatment and variation of the welding current; (3) to obtain the level of violence before and after welding the MIG method with preheating treatment and welding current variations; (4) to obtain the level of impact toughness before and after welding the MIG method with preheating treatment and welding current variations. The study was conducted by taking specimens from the cast wheel in accordance with the research standards used, then welding the MIG method using the ER4043 electrode with preheating treatment and current variations of 90 A, 100 A, and 110 A. The data analysis technique in this study used descriptive data analysis. Analyzing data includes testing the chemical composition, microstructure, price of hardness, impact toughness. Based on the results of the study it can be concluded that: (1) The chemical composition of the cast wheel is Aluminum (Al) 91.74%, Silicon (Si) 7.62% This cast wheel is a type of aluminum series AA4343; (2) The microstructure of the aluminum cast wheel shows that variations in the welding current will affect the size of the aluminum and silicon grains; (3) The hardness value in raw material specimens is 96 HV while the highest hardness value in the welding area is at 100 A welding current which is 60.2 HV, while the lowest hardness value is at 90 A welding current which is 52.0 HV; (4) The value of impact toughness on raw material specimens is 0.45 J / mm2. The lowest impact toughness value with 100 Amperes current is 0.46 J / mm2 and the highest impact toughness value with 110 Amperes current is 0.52 J / mm2.